Pendampingan Manajemen Organisasi Musholla untuk Meningkatkan Literasi Keislaman Masyarakat Dusun Pesisir Timur, Desa Dharma Camplong, Kecamatan Camplong, Kabupaten Sampang - abdullah (ABDI MASYARAKAT, 2025)
The musholla (small Islamic prayer room) as the closest religious institution to coastal communities has not yet played an optimal role in enhancing contextual Islamic literacy. This program aims to empower the organizational management of the musholla through intensive mentoring so it can become a catalyst for increasing comprehensive, moderate, and applicable Islamic literacy. This community service initiative uses a participatory method with a thematic approach, through five stages of activity: 1) Preparation (Networking & Securing Permits, Observation, Coordination & Identification of Strategic Islamic Literacy Themes). 2) Participatory Planning (Initial Islamic Literacy Survey, Designing the Program & Activity Schedule, Role Division). 3) Implementation (Activity Socialization, Islamic Literacy Activities According to Themes, Attendance Tracking). 4) Evaluation (Final Survey, Joint Reflection with the Management Board). 5) Follow-up (Independent Mentoring for the Management Board, Closing Ceremony & Appreciation, Signing of a Memorandum of Understanding (MoU). Results of the Initiative: 1) Increased managerial capacity of the musholla management board in conducting Islamic literacy activities for the congregation. 2) Increased knowledge capacity on the theme of Islamic inheritance law (faraidh), from 18% (very low) to 55% (fairly good). 3) The establishment of an organizational commitment to continue carrying out the activities sustainably in the future.